Oral anaerobe bacteria—a common risk for cardiovascular disease and mortality and some forms of cancer? - Lund Håheim, Anne Lise (Frontiers in Oral Health, 2024)
This review explores the results of research on oral health concerning cardiovascular diseases and some forms of cancer and is based on results from published systematic reviews and some studies. The research results will have a strong focus on exploring the relationship between different aspects of oral infections. The relationship between oral health parameters, cardiovascular diseases, and certain cancers, was examined from different angles, including prospective analyses, in the population-based health study in Oslo from the year 2000 (Oslo II study). A major finding was that low levels of antibodies to the oral anaerobe Tannerella forsythia predict both cardiovascular disease (CVD) mortality in men with a history of myocardial infarction and incidence of bladder cancer in a random sample of men in the study. Low levels of antibodies to Treponea denticola predict the incidence of bladder and colon cancer in a random sample of men in the study. Both anaerobe bacteria are part of the so-called red complex of bacteria in chronic periodontitis together with Pophyromonas gingivalis. These three bacteria have different properties and are causal in chronic periodontitis. They migrate into the local tissues by adhering to the oral epithelium, break down soft and hard tissues, and spread via the circulation to organs distant from the mouth. This paper will give an overview of which oral health measures have been explored and associated with different CVD and cancer diagnoses and what scientific literature supports or contravenes our hypothesis.The oral microbiome is described with the most relevant bacteria related to microbiology, serum, autopsies, and associated causes such as alcohol. There will be a mention of the possibilities and limitations of different study designs. There seems to be a causal relationship between oral anaerobe bacteria and systemic diseases regulated by the immune system. This is seen alongside other well-known risk factors, especially for CVD. The prospective finding of a relation to the incidence of certain cancers and CVD is particularly intriguing. However,